The first rector of IIUM in the words of the third rector - Hassan @ Mohamed, Nor Jana (OFIIR-CENTRIS, 2024)
Part of the efforts in getting to know more about the University is to know her Rectors well. The following account highlights the stature and personality of the IIUM’s first Rector, from the words of the third Rector – both of whom had coloured the identity and ethos of the International Islamic University Malaysia, which in turn had brought the University in her fledgling years to solid international and ummatic recognitions.